Studies on Er2O3/Dy2O3 doped zinc borotellurite glasses - Kaur, Sandeep (My University, 2022)
Rare earth (RE3+) elements are well known for their exceptional properties and industrial applications. They play important role in the modern optoelectronic industries. RE doped glasses have many applications such as in high power lasers and as radiation shielding materials. Most of the glass lasers use RE3+ ions as active sites because of low coupling of the RE3+ with the host vibrations. The host required for laser applications must have very less phonon energy. For this purpose tellurite glasses are considered as excellent choice because of their least phonon energy amongst all the other oxide glasses. The present work deals with the preparation of Er2O3/Dy2O3 doped zinc borotellurite glasses. The effect of different processing conditions like heat treatment and gamma irradiation on the structural, optical and luminescent properties of such glasses is studied in detail. The entire thesis is divided into eight chapters; the outline of each chapter is given below: Chapter 1 The optical properties of the RE doped glasses are important for their applications. The present chapter describes the luminescence properties of materials and their associated mechanisms. Since the work deals with tellurite and borate glasses a brief introduction of glasses and their properties which get affected by heat treatment and gamma irradiation have been presented in this chapter. Chapter 2 summarizes the literature review on the tellurite glasses. This chapter gives introduction about the work done by different researchers to prepare pure tellurite glasses. It also discusses about the discrepancies found in various parameters like transition temperature and density of pure TeO2 glasses. In continuation it discusses about the mixed former and effect of modifiers on the tellurite glasses. This chapter also gives information about the effect of dopants like rare earths and metal nano particles on the luminescent properties of the tellurite glasses. Discussion about the effect of heat treatment and gamma irradiation on different properties of TeO2 glasses is also done in this chapter. After analyzing the work done so far, the gaps in study has been highlighted and accordingly, the objectives of the present study are proposed. Chapter 3 gives the details about sample preparation and the various characterizations done in the present study. The chapter discusses about the preparation of Er2O3/Dy2O3 doped zinc borotellurite glasses in detail. The parameters adopted for characterization techniques such as X-ray diffraction (XRD), differential thermal analysis (DTA), field emission scanningelectron microscopy (FESEM), UV-Vis-NIR absorption spectroscopy, Photoluminescence (PL) spectroscopy are given in this chapter. Chapter 4 illustrates the spectroscopic studies of erbium zinc borotellurite glasses and glass-ceramics. The concentration of Er2O3 is varied from 0 to 2.5 mol%. In order to convert the glasses to glass ceramics, thermal studies are done to choose a temperature range for heat treatment. In order to optimize time and temperature, glass sample with 0.5 mol% Er2O3 is given heat treatment at 375, 400 and 450 oC for 2, 4 and 6h. Since the maximum PL intensity has been observed for the sample heat treated at 400 oC for 4h, all the glasses are heat treated at 400 oC for 4h. Further, the effect of heat treatment on the structural and various radiative properties on the glasses is discussed in detail. Chapter 5 discusses about the spectroscopic, thermal and structural properties of Dy2O3 on the zinc borotellurite glasses and glass-ceramics using DTA, XRD, FESEM, Raman spectroscopy, UV-Vis-NIR spectroscopy, PL, and decay time measurements. The optimization of the thermal parameters in order to covert glasses into glass ceramics is done as explained in the Chapter 4. Chapter 6 discusses about the effect of 50 kGy gamma irradiation on the thermal, structural and spectroscopic properties of the Er2O3 doped glasses. The chapter also discusses it’s applications as shielding material and shielding properties of the present glasses in detail. Chapter 7 discusses about the effect of 50 kGy gamma irradiation on the thermal, structural and spectroscopic properties of the Dy2O3 doped glasses. The chapter further discusses about the effect of increasing Dy2O3 concentration on the shielding properties of the present glasses in detail. Chapter 8 summaries the results obtained in the Chapter 4, 5, 6 and 7. The effect of different processing conditions like heat treatment and gamma irradiation on the spectroscopic properties of Er2O3/Dy2O3 doped glasses is discussed and compared. At the end suggestions for the future work is also given in this chapter.
Keywords: TeO2 glasses; glass ceramics; RE spectroscopy; crystal field splitting; Raman spectroscopy